2015
DOI: 10.1007/s12540-015-5093-3
|View full text |Cite
|
Sign up to set email alerts
|

Hot tensile deformation behavior of twin roll casted 7075 aluminum alloy

Abstract: High temperature deformation behavior of the 7075 aluminum alloy sheets fabricated by twin roll casting and rolling was investigated by hot tensile tests at different temperatures from 350 to 500°C and various initial strain rates from 1×10 -3 to 1×10 -2 s -1. The results show that flow stress increased with increasing initial strain rate and decreasing deformation temperature. A large elongation of 200% was obtained at relatively high strain rate of 5×10 -3 s -1 at 450°C. It is closely related with the grain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 34 publications
0
7
0
1
Order By: Relevance
“…As a general trend, fracture strain rises with the elevation of temperature at each strain rate in Figure 2 . It can be found that flow stress rises with the increasing of strain rate at given temperature, as depicted in Figure 3 , mainly due to the enhanced deformation storage energy [ 5 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a general trend, fracture strain rises with the elevation of temperature at each strain rate in Figure 2 . It can be found that flow stress rises with the increasing of strain rate at given temperature, as depicted in Figure 3 , mainly due to the enhanced deformation storage energy [ 5 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, high contents of alloying elements may simultaneously weaken the hot workability of the alloy [ 1 ]. It has been widely acknowledged that deformation mechanisms of work hardening (WH) [ 2 , 3 ], dynamic recrystallization (DRX) [ 4 , 5 ], and dynamic recovery (DRV) [ 6 , 7 ] can result in different deformation behavior of Al-Zn-Mg-Cu alloy. Therefore, the problem of how to enhance the mechanical properties and optimize the formability of Al-Zn-Mg-Cu alloy has become a research hotspot in recent years, and some researches have been made to explore its hot deformation behaviors at quasi-static strain rate [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At high temperatures from 350 to 500°C and strain rates from 1 × 10 −3 to 1 × 10 −2 s −1 , hot tensile test was performed. The results showed that by increasing the strain rate and decreasing deformation temperature, flow stress was increased [9]. Similarly, three aluminum alloys containing different silicon contents were studied at a temperature range of 573-773 K with strain rates of 0.01, 0.1, 1 and 5 s −1 [10].…”
Section: Aluminum Alloy Behavior During Hot Formingmentioning
confidence: 99%
“…또한 용체화 처리 후 자연시효된 7075 합금을 소부경화처리할 경우, 불균일하고 조대한 시효 석출상 (MgZn 2 )이 형성되어 강도 상승을 저해하는 것으로 보고되 었다 [13]. 또한 기존 차체용으로 사용되는 Al-Mg-Si계 합 금의 경우에는 예비시효(Pre-aging) [3,15,16] 및 예비변형 정도로 매우 크기 때문에 미세한 주조 조직을 얻을 수 있으며, 정출상의 크기를 미세화할 수 있는 장점 이 있다[19,20]. 전기로를 사용하여 720 o C에서 Al, Zn C에서 1시간 열처리 후, 두께 3.0 mm까지 열간압연을 행하였다.…”
unclassified